2001
DOI: 10.1085/jgp.118.4.355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dantrolene on Steps of Excitation-Contraction Coupling in Mammalian Skeletal Muscle Fibers

Abstract: The effects of the muscle relaxant dantrolene on steps of excitation-contraction coupling were studied on fast twitch muscles of rodents. To identify the site of action of the drug, single fibers for voltage-clamp measurements, heavy SR vesicles for calcium efflux studies and solubilized SR calcium release channels/RYRs for lipid bilayer studies were isolated. Using the double Vaseline-gap or the silicone-clamp technique, dantrolene was found to suppress the depolarization-induced elevation in intracellular ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
92
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 46 publications
9
92
0
Order By: Relevance
“…13). This is necessary in bilayer studies to remove the resting inhibition on the RyR and induce a measureable opening probability in the isolated channel.We hypothesized that the lack of dantrolene action on single RyRs was due to the fact that the experiments were carried out either in the absence of or in low free [Mg 2+ ] cyto (26,30,31). In contrast, the intact fiber experiments, where dantrolene inhibited the RyR, maintained the endogenous level of free [Mg 2+ ] cyto (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13). This is necessary in bilayer studies to remove the resting inhibition on the RyR and induce a measureable opening probability in the isolated channel.We hypothesized that the lack of dantrolene action on single RyRs was due to the fact that the experiments were carried out either in the absence of or in low free [Mg 2+ ] cyto (26,30,31). In contrast, the intact fiber experiments, where dantrolene inhibited the RyR, maintained the endogenous level of free [Mg 2+ ] cyto (26).…”
mentioning
confidence: 99%
“…Functional studies on muscle fibers suggested the RyR as the potential target for the action of dantrolene (25,26), and respective binding sites were mapped to the protein (27)(28)(29). However, no action of dantrolene was found in most studies on single RyRs incorporated into lipid bilayers (26,30,31).…”
mentioning
confidence: 99%
“…Although dantrolene has been shown to suppress the ryanodine binding activity of the SR (13,14), this finding is not universal (15). Dantrolene (1-5 M) has been reported to have a biphasic effect on the open probability of RyR1 channels in lipid bilayers, first activating and then blocking at nanomolar concentrations (16), but others have not been able to see any effect of this drug on single channels (3). Importantly, dantrolene has been shown to at least partially restore the normal properties of RyR1 Ca 2ϩ channels in SR isolated from MH-susceptible pigs (1,17,18).…”
mentioning
confidence: 99%
“…1 MH is a potentially deadly, pharmacogenetically mediated, hypermetabolic response to volatile anesthetics that results from unregulated intramyoplasmic Ca 2ϩ release (1). The drug is known to inhibit excitation-contraction coupling of skeletal muscle (2) by suppressing depolarization-induced sarcoplasmic reticulum (SR) Ca 2ϩ release in normal and MH-susceptible skeletal muscle without affecting voltage sensor activation (3). In MH, the voltage dependence of contractile activation is shifted to lower voltages (4), whereas in the presence of clinical concentrations of dantrolene, i.e.…”
mentioning
confidence: 99%
“…Dantrolene has been shown to directly bind to the N-terminus of RyR1 and to prevent SR Ca 2+ leak in skeletal muscle, thereby improving clinical outcomes [29] . Dantrolene is believed to stabilize interdomain interactions between the N-terminal and central domains of RyR1 [30] and RyR2 [31] , although the effects of dantrole on single RyR channels remains controversial [32] .…”
Section: Dantrolenementioning
confidence: 99%